Effect of ethanol extract of nigella sativa L seeds and propofol on BDNF protein level as neuroplasticity and neuroprotection of traumatic brain injury in rats [version 2; peer review: 1 approved, 2 approved with reservations] - Kulsum Kulsum; Syahrul Syahrul; Kartini Hasbalah; Ummu Balqis (F1000Research)
Background Traumatic brain injury (TBI) is a change in brain function or evidence of brain pathology caused by external mechanical forces. Brain Derived Neurotrophic Factor (BDNF) is a neurotropin that functions as a neuron protective. Nigella sativa L is reported to have an antioxidant effect, administration of Nigella Sativa L to rats treated with ischemia-reperfusion brain injury. Propofol is an anesthetic agent frequently used intravenously in the management of TBI. The effect of propofol on brain tissue after TBI may be neuroprotective. We aimed to compare the potential of Nigella sativa L and propofol as neuroplasticity and neuroprotection in rats with TBI. Methods This was a laboratory experimental animal model with the post-test only control group design, namely measuring the effect of treatment by comparing the five groups of rats consisting of 30 rats. BDNF levels in rat brain tissue were collected at day 7 of treatment and measured by ELISA. Results The average BDNF protein levels per group, namely G1 (221,243 pg/mL), G2 (172,139 pg/mL), G3 (255,483 pg/mL), G4 (227,089 pg/mL), and G5 (272,603 pg/mL) respectively. Based on the ANOVA statistic, p-value = 0.032 (there was a significant difference between groups), with the Levene Test (0.077) or having variance between the same groups, sequentially the difference in average BDNF protein levels of the five groups is G5>G3>G4>G1>G2, meaning that the combination of Nigella sativa and propofol has more potential to increase BDNF protein levels than Nigella sativa, and Nigella sativa has more potential than propofol. Conclusion We concluded that both nigella sativa and propofol have the potential to increase BDNF protein levels. Nigella Sativa L had a better effect than propofol in repairing damaged neuron cells (neuroplasticity) and increasing BDNF protein levels (neuroprotection) for 7 days of administration in rat traumatic brain injury.